-14=-2n

Rewrite the equation as -2n=-14.

-2n=-14

Divide each term in -2n=-14 by -2.

-2n-2=-14-2

Cancel the common factor of -2.

Cancel the common factor.

-2n-2=-14-2

Divide n by 1.

n=-14-2

n=-14-2

Divide -14 by -2.

n=7

n=7

Solve for n -14=-2n

Skip to content
# Solve for n -14=-2n

-14=-2n

Rewrite the equation as -2n=-14.

-2n=-14

Divide each term in -2n=-14 by -2.

-2n-2=-14-2

Cancel the common factor of -2.

Cancel the common factor.

-2n-2=-14-2

Divide n by 1.

n=-14-2

n=-14-2

Divide -14 by -2.

n=7

n=7

Solve for n -14=-2n